The Art of Modelling Computational Systems : a journey from logic and concurrency to security and privacy : Essays Dedicated to Catuscia Palamidessi on the Occasion of Her 60th Birthday /: a journey from logic and concurrency to security and privacy : Essays Dedicated to Catuscia Palamidessi on the Occasion of Her 60th Birthday. ([2019]) - Unknown
No abstract available